2019
DOI: 10.1007/s40544-019-0303-5
|View full text |Cite
|
Sign up to set email alerts
|

Friction-condition-dependent sulfide and sulfate evolution on dialkylpentasulfide tribofilm studied by XANES

Abstract: The effects of friction conditions, such as rotational speed, frictional time, and applied load, on the evolution mechanism of sulfide and sulfate on the top and bottom layers of tribofilm were investigated by total electron yield (TEY) and fluorescence yield (FY) mode X-ray absorption near-edge structure (XANES) spectra in the same beam line (4B7A). The results demonstrated that the top and bottom layers of tribofilms were covered by sulfide and sulfate. The addition of dialkylpentasulfide (DPS) could form co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Numerous studies have claimed that, ZDDP additive occupies a relatively smaller portion of formulated lubricant, it can protect the surface from wear through forming a protective boundary layer consisting of adaptive polyphosphate/sulfide composite on the steel substrate, 34 which is definitely coming from the interaction of surface‐active ZDDP additive with the ferrous tribosurfaces 35 . In particular, when subjected to higher loading conditions, the tribofilm composition becomes iron–sulphur compound dominant 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have claimed that, ZDDP additive occupies a relatively smaller portion of formulated lubricant, it can protect the surface from wear through forming a protective boundary layer consisting of adaptive polyphosphate/sulfide composite on the steel substrate, 34 which is definitely coming from the interaction of surface‐active ZDDP additive with the ferrous tribosurfaces 35 . In particular, when subjected to higher loading conditions, the tribofilm composition becomes iron–sulphur compound dominant 11 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the tribochemistry reaction during the sliding process, XANES was used to investigate protective tribofilms (after friction) on the worn surface. The K-edge spectra of standard compounds were used to identify the chemical nature of the tribofilm on the worn surface, thus revealing the lubrication mechanism . The spectra of several model compounds as fingerprints for the S K-edge were obtained in the literature (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The K-edge spectra of standard compounds were used to identify the chemical nature of the tribofilm on the worn surface, thus revealing the lubrication mechanism. 36 The spectra of several model compounds as fingerprints for the S K-edge were obtained in the literature 37 (see Table 2). Here, we show the sulfur K-edge XANES spectra of the polymers before the sliding process and the tribofilms generated from PIBOA and PMMA in Figure 8.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, table 3 shows that the mass percentage of zinc and sulfur is higher than that of phosphorus. The higher mass percentage of zinc and sulfur suggests that these elements might be concentrated in the outer layers or specific strata of the tribofilm [16,30]. 3.1.2.…”
Section: Wear Properties 311 Effect Of Zddp Concentration On Wearmentioning
confidence: 99%
“…Hsu [15] demonstrated that under high pressure, tribofilm exhibits a zinc-rich tribofilm, an oxide layer, and sulfur enrichment, with a higher zinc content observed in the upper part and increased iron content in the lower part of the tribofilm. Ganlin Zhang [16] utilized x-ray absorption near-edge structure (XANES) spectra to investigate the evolution mechanism of sulfide and sulfate in the top and bottom layers of tribofilm, showing highlighting the prevalence of sulfate over sulfide on the tribofilm's upper surface.…”
Section: Introductionmentioning
confidence: 99%